Characterising acute and chronic care needs: insights from the Global Burden of Disease Study 2019 - Anza-Ramirez, Cecilia; Jonas, Jost B. (Nature Communications, 2025)
Chronic care manages long-term, progressive conditions, while acute care addresses short-term conditions. Chronic conditions increasingly strain health systems, which are often unprepared for these demands. This study examines the burden of conditions requiring acute versus chronic care, including sequelae. Conditions and sequelae from the Global Burden of Diseases Study 2019 were classified into acute or chronic care categories. Data were analysed by age, sex, and socio-demographic index, presenting total numbers and contributions to burden metrics such as Disability-Adjusted Life Years (DALYs), Years Lived with Disability (YLD), and Years of Life Lost (YLL). Approximately 68% of DALYs were attributed to chronic care, while 27% were due to acute care. Chronic care needs increased with age, representing 86% of YLDs and 71% of YLLs, and accounting for 93% of YLDs from sequelae. These findings highlight that chronic care needs far exceed acute care needs globally, necessitating health systems to adapt accordingly.
Mitlgieder der GBD 2019 Acute and Chronic Care Collaborators: Cecilia Anza-Ramirez, J. Jaime Miranda, Benedetta Armocida, Jorge César Correia, Harriette Gillian Christine Van Spall, David Beran, Amirali Aali, Jost B. Jonas [...und viele weitere]
Gesehen am 17.11.2025